Physical Potential Hazards On The Palm Oil Processing Of PT.Perkebunan Nusantara VII 2019 - Ikhssani, Agung (Preventif : Jurnal Kesehatan Masyarakat, 2019)
Identification of potential hazards is the basis of modern occupational safety management and hazards can threaten whenever and wherever including the agricultural sector. To develop the economic strength of the agricultural sector, it is necessary to increase productivity. One way that can be done is to increase employee productivity through the Employee Safety and Health program. The purpose of this study was to determine the potential physical hazards in the PPKS PTPN VII Bekri Business Unit. This type of research is interviews and observations that aim to find an overview of the assessment of physical potential hazards in the palm oil processing PT. Perkebunan Nusantara VII Bekri business unit. The physical potential hazards found in the Palm Oil Processing Plant (PPKS) are the potential hazards of noise generated by machines> 85dB, hot working climate inside the factory, vibrations from the processing process, and improper lighting in the factory. Physical potential hazards contained in the PPKS unit are auditory and non-auditory disturbances on the dangers posed by noise, headaches and dehydration as well as attacks that can arise due to heat, discomfort due to inappropriate lighting resulting in potential work accidents and the appearance of musculoskeletal disorders due to a potential vibration hazard